ANALYSIS OF THE EFFECT OF DIVIDEND PAYOUT RATIO AND FIRM SIZE ON COMPANY VALUE WITH PROFITABILITY AS A MEDIATING VARIABLE IN THE ENERGY SECTOR ON THE INDONESIA STOCK EXCHANGE - Willa Fatika Sari; Darman Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of Dividend Payout Ratio (DPR) and Firm Size on Company Value (PBV) with Profitability (ROE) as a mediating variable in energy sector companies on the Indonesia Stock Exchange for the 2018–2024 period. The method used is Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that DPR and Firm Size did not have a significant effect on ROE or PBV, and ROE also did not have a significant effect on PBV. Thus, ROE does not mediate the relationship between these variables. The insignificance of this influence reflects the characteristics of the energy sector which is volatile, capital-intensive, and facing a new and renewable energy transition. Investors pay more attention to asset efficiency, sustainable profitability, and capital structure than dividend policies or company scale.